If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(-8) = 0 Multiply 3 * -8 2x + -24 = 0 Reorder the terms: -24 + 2x = 0 Solving -24 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 2x = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 2x = 0 + 24 2x = 0 + 24 Combine like terms: 0 + 24 = 24 2x = 24 Divide each side by '2'. x = 12 Simplifying x = 12
| 15x-2.4x=0.6+7.6x | | -4(x)-2y=-12 | | 25p^2-4=0 | | 5x=40*0.5 | | a=h(b+c)solve(b) | | 2x+5(x-1)= | | 3(-11)[5(-3)-7(-2)]= | | 6xrqw+13xrqw=133 | | 9s-36=5s | | 64g^3-125h^3=0 | | 13(x-4)=8x-32 | | 16t^2=-h+100 | | 3/4+1/4x=3/4x-1/4 | | -4=3n-7n | | 2x-60=x | | x-2=14*2 | | 16t^2+h=100 | | 1-11-3x=32 | | x+by=c*x | | (2m-7)squared= | | 2(7)-2x=6 | | 12x-4(3x)=0 | | 4b-8b^2=0 | | x/2-1/5=x/3+1/4 | | Y+5/8=-2 | | -17x=391 | | 7y-18=-46+3y | | 6(1)-10x=77 | | 2x-5(x-2)=-6+3x-20 | | -6(8+5n)-5=6n+19 | | (8xy-y)(8xy-y)= | | 7y-10(6y-13)=77 |